Apartment selection by college students: Do Americans and Asians use different criteria, information sources, and media?. Issue 1 (23rd March 2020) - Smith, Katherine Taken; Pinkerton, Austin
Abstract : Purpose: The purpose of this paper is to examine the apartment preferences of American and Asian college students, the sources of information they use when searching for an apartment and the media that influence their buying decision. This study examines determinant criteria in conjunction with the theory of consumption values and utilitarian versus hedonic attributes. Design/methodology/approach: Data was collected from multiple apartment complexes in a metropolitan area of approximately 250, 000 people with over 70, 000 college students. All residents of the apartment complexes were asked to answer an online questionnaire. From those questionnaires, a total of 865 qualified to be in the sample for this research study. Qualification depended on the respondent being a college student and of either American or Asian nationality. Findings: The apartment attributes that are found to be determinant criteria for college students are categorized according to whether they provide utilitarian or hedonic value. These two values relate to the functional and emotional values within the theory of consumption values. The majority of the apartment attributes identified as determinant criteria provide utilitarian value. Specific apartment attributes are described in the paper. The main apartment attributes for which Asian students differ from Americans center on the Asians' desire for security and accessibility to where they want to go. Practical implications: With a rising number of people renting instead of buying a home, apartment complexes continue to multiply. The majority of renters are single persons, thus, the majority of apartments should be designed to appeal to the preferences of singles. College students, both native and international, are part of this coveted consumer market. Hence, developers and marketers would be wise to consider the housing preferences of college students. Originality/value: This paper contributes original information in two areas pertaining to the development and marketing of apartments: the preferences of American college students and the preferences of Asian college students.